2016
DOI: 10.1101/072603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pleiotropy-robust Mendelian Randomization

Abstract: Background: The potential of Mendelian Randomization studies is rapidly expanding due to (i) the growing power of GWAS meta-analyses to detect genetic variants associated with several exposures, and (ii) the increasing availability of these genetic variants in large-scale surveys. However, without a proper biological understanding of the pleiotropic working of genetic variants, a fundamental assumption of Mendelian Randomization (the exclusion restriction) can always be contested. Methods:We build upon and syn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 61 publications
1
46
0
Order By: Relevance
“…It thereby provides a well‐informed way to perform sensitivity analyses in IV estimation. In a companion epidemiological paper (van Kippersluis and Rietveld, ), we applied this idea in the context of genetic variants as instrumental variables. Here we apply the approach in general IV settings, and illustrate our procedure by estimating the effect of (a) attending Catholic high school on schooling outcomes and (b) the number of children on female labour supply.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It thereby provides a well‐informed way to perform sensitivity analyses in IV estimation. In a companion epidemiological paper (van Kippersluis and Rietveld, ), we applied this idea in the context of genetic variants as instrumental variables. Here we apply the approach in general IV settings, and illustrate our procedure by estimating the effect of (a) attending Catholic high school on schooling outcomes and (b) the number of children on female labour supply.…”
Section: Introductionmentioning
confidence: 99%
“… An intuitive example is discussed in van Kippersluis and Rietveld ( ), where certain genetic variants are used as IVs for prostate cancer to study its effect on self‐reported health. Since prostate cancer naturally is only a risk factor among males, the first stage among females is zero by construction.…”
mentioning
confidence: 99%
“…The idea is to identify a sample over which it is known, preferably by design, that the candidate IV is not related to the treatment. For example, van Kippersluis and Rietveld discussed an application where certain genetic variants are used as IVs for prostate cancer to study its effect on self‐reported health. Because prostate cancer is a risk factor only for males, females provide such a sample.…”
Section: Discussionmentioning
confidence: 99%
“…Conley et al(17) emphasise the potential trade-off between instrument strength and degree of IV3 violation in putting forward the notion of plausibly endogeneity, whilst further works underlining the utility of using instrument-covariate interactions have also emerged, such as those of Gennetian et al and Small(18, 19). It is also worth noting that a similar method, entitled Pleiotropy Robust Mendelian Randomization (PRMR), has recently been put forward with a similar intuitive framework(20). However, the PRMR approach requires a subgroup for which the instrument and the exposure are independent to be observed, potentially limiting the applicability of the approach in contrast to approaches which estimate the expected association at a hypothetical independent subgroup.…”
Section: Introductionmentioning
confidence: 99%